LAND SUBSIDENCE DUE TO WITHDRAWAL OF DEEP-GROUNDWATER - Shen S.-L; Tohno I; Nishgaki M.; Miura N. (Lowland Technology International, 2004)
This paper presents a case history of land subsidence due to withdrawal of groundwater from deep marine sediments at the mid-northern part of Boso Peninsula, Chiba, Japan. Since 1969, subsidence has been observed in a large area. The maximum accumulative subsidence in the past 33 years has been about 0.85 m. In order to obtain overall information, 3D FEM analysis was conducted to calculate the land subsidence resulting from extraction of deep-ground water. The calculation method is based on the theory of groundwater flow through saturated and unsaturated media. This in an uncoupled approach for consolidation analysis. The compressibility of ground is considered in the calculation. In the calculation, the behavior of hydraulic conductivity and the compressibility of reservoir rock (Plio-Pleistocene sediments) under high presure were determined by laboratory odometer test and take into consideration. The analytical results were compared with the field-observed data. The results showed that this approach simulated the field case fairly well.